2022
DOI: 10.3389/fimmu.2022.858722
|View full text |Cite
|
Sign up to set email alerts
|

miR-144-3p Is a Biomarker Related to Severe Corticosteroid-Dependent Asthma

Abstract: MicroRNAs are non-coding molecules that act both as regulators of the epigenetic landscape and as biomarkers for diseases, including asthma. In the era of personalized medicine, there is a need for novel disease-associated biomarkers that can help in classifying diseases into phenotypes for treatment selection. Currently, severe eosinophilic asthma is one of the most widely studied phenotypes in clinical practice, as many patients require higher and higher doses of corticosteroids, which in some cases fail to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…Our group previously used NGS to describe 15 miRNAs differentially expressed between eosinophilic and non-eosinophilic asthmatic patients, two of which were validated and could serve as instruments to classify patients into different phenotypes/endotypes [ 15 ]. In addition, hsa-miR-144-3p was previously described by our group to present an increase in miRNA levels in corticosteroid treated subjects by RT-qPCR [ 27 ], which validates the result obtained in miRNAs-Seq from the lung biopsy samples of asthmatics.…”
Section: Discussionsupporting
confidence: 80%
“…Our group previously used NGS to describe 15 miRNAs differentially expressed between eosinophilic and non-eosinophilic asthmatic patients, two of which were validated and could serve as instruments to classify patients into different phenotypes/endotypes [ 15 ]. In addition, hsa-miR-144-3p was previously described by our group to present an increase in miRNA levels in corticosteroid treated subjects by RT-qPCR [ 27 ], which validates the result obtained in miRNAs-Seq from the lung biopsy samples of asthmatics.…”
Section: Discussionsupporting
confidence: 80%
“…Faiz et al used airway biopsies from subjects with COPD and reported elevated miR-320d during ICS treatment compared to placebo, as this miRNA reduced cigarette smoke extract-induced inflammation by NF-κβ inhibition [ 106 ]. Regarding this matter, we found that expression of miR-144-3p was increased in the serum and lung tissue of asthmatics, and that this expression augmented with corticosteroids, hence making it a biomarker for severe asthma treated with higher doses of corticosteroids (AUC = 0.74) [ 107 ].…”
Section: Mirnas and Their Relation To Asthma Treatments And Optimal R...mentioning
confidence: 99%
“…Another study demonstrated a higher concentration of miRNA-144-3p in severe disease and its positive correlation with blood eosinophilia. This biomolecule affects genes responsible for the inflammatory process and remodeling of the airways, e.g., GATA3, STAT6, SOCS5, RHOA, NR3C1, and PTEN, which makes it a potential diagnostic marker for severe asthma [ 20 ]. In non-allergic asthma, miRNA-629-3p, miRNA-223-3p, and miRNA-142-3p were significantly elevated in patients with severe symptoms and associated with increased inflammation mediated by neutrophils.…”
Section: The Diagnostic Role Of Mirnasmentioning
confidence: 99%